MODERN METHODS OF TEACHING ENGLISH - Mirkhodjayeva Mahliyo Islamovna; Bobokulova Gulrukh Sharipovna (Galaxy International Interdisciplinary Research Journal, 2022)
The world has changed markedly in recent decades, and the knowledge of foreign languages is becoming an urgent need in it, and English, as you know, is one of the most frequently studied. And the more people who want to study it, the more new methods appear, so everyone can find the best solution for themselves. Methodology in a general sense means a set of means and methods of teaching. One prefers to learn on his own, the other is more comfortable with outside help and control, not to mention how the program for teaching children at home, in kindergarten or at school is built. The article analyzes the possibilities of using modern methods in the process of teaching a foreign language. The main classifications of methods are carried out, allowing the most effective help in teaching English.